Quantitative Evaluation of Post-stenotic Blood Flow Disturbance in Canine Femoral Artery Stenosis Model: An Early Experience With Vector Flow Imaging - Zhao, Rui; Zheng, Haining; Wang, Wei; Du, Yigang; Tong, Yisha; Wen, Chaoyang (Frontiers in Cardiovascular Medicine, 2022)
Objective: To investigate the value of Vector Flow Imaging (V Flow) in the assessment of post-stenotic turbulence in the canine arterial stenosis model. Materials and methods: Canine femoral artery stenosis models were established using ameroid constrictors in 12 beagle dogs. 50% and then 70% femoral artery stenoses were confirmed by selective femoral artery angiography. V Flow was used to measure femoral artery flow turbulence index (Tur) preoperatively as a baseline. After establishing of a 50% and then 70% stenoses, the Tur indices were recorded in the femoral artery at 1 mm, 3 mm, 5 mm, 7 mm, 9 mm, 11 mm, 13 mm, 15 mm, 17 mm, and 19 mm distal to the stenosis. Results: Baseline Tur indices of normal canine femoral arteries were less than 1% in 11 of 12 cases (91.7%). Distal to a 50% stenosis, the Tur index (>1%) was recorded in 83.3-100% cases between 1 mm and 9 mm, 41.7-58.3% between 11 and 17 mm, and 16.7% at 19 mm. For a 70% stenosis, the Tur index (>1%) occurred in 81.8-100% cases between 1 mm and 17 mm distal to the stenosis, and 63.6% at 19 mm. The Tur index peaked around 7 mm or 2.3 times of the initial vessel diameter (3 mm) downstream for a 50% stenosis and 11 mm or 3.7 times of vessel diameter downstream for a 70% stenosis. Conclusion: V Flow with Tur index measurement adds quantitative information of post-stenotic turbulence when assessing an arterial stenosis with ultrasound. Tur index of 1% seems a useful threshold for assessment of flow turbulence in this small sample study. Further studies with larger sample size are needed to evaluate the value of V Flow in clinical applications.